Exploring Career Pathways: in-Depth Analysis of Hiring Trends and Career Growth in the IT and Food & Beverage Industries - Vidhi Sheth; Himani Solanki; Jignesh Vidani (MultiTech Publisher, 2024)
The food and beverage technology sector is rapidly evolving, creating new career opportunities and demanding a diverse skill set. This study explores job roles, required skills, salary trends, and growth prospects in this industry, focusing on two leading companies—Petpooja and Ajay’s Good Food. Through an in-depth analysis of hiring patterns, technical and soft skills required, and career progression pathways, this paper highlights key insights for fresh graduates and professionals looking to enter or advance in this field. The findings indicate that roles in software development, sales, customer support, and digital marketing are in high demand. Technical knowledge of POS systems, cloud computing, and AI-driven analytics is becoming increasingly valuable. Additionally, strong communication, adaptability, and problem-solving skills are crucial for success. The research also identifies factors influencing salary growth and promotions, as well as the importance of certifications and training programs in improving employability. Emerging trends, such as automation, AI-driven customer insights, and data analytics, are reshaping the job market, requiring continuous skill enhancement. Furthermore, industry competition and globalization are pushing companies to seek innovative talent with a strong technological acumen. By examining these industry dynamics, this paper provides valuable guidance for job seekers, HR professionals, and policymakers to align workforce development with market needs